Analisis Tingkat Pemahaman Konsep dan Miskonsepsi Fisika pada Pokok Bahasan Alat-alat Optik di SMA Negeri 1 Purwodadi - Purwaningtias, Wulan Sari; Putra, Ngurah Made Dharma (UPEJ Unnes Physics Education Journal, 2020)
This study aims to determine the level of understanding of the concept, the level of misconception, and the factors causing misconceptions that occur in students of class XI MIPA 2 in SMA Negeri 1 Purwodadi. This research is a mixture of qualitative and quantitative research. The instrument used in this study was a check-list; written test questions that are equipped with student confidence tables in answering questions or the Certainly Of Response Index (CRI); and interview guide sheets. The data collected is then analyzed to determine the students who will take the interview. Interviews were conducted with 9 students who had different levels of concept understanding. Furthermore, data from written test results and interviews are interpreted together with triangulation techniques to obtain conclusions from the research results. The analysis showed that the level of understanding of the concept of class XI students in SMA Negeri 1 Purwodadi on optical equipment material had a percentage of concept understanding of 16%, misconceptions of 55%, and did not understand the concept of 29%. The highest misconception is in the matter of the nature of mirrors and convex lenses in everyday events and special rays in convex mirrors with a percentage of 61%. Factors causing misconceptions among students include examples of questions given by teachers less varied, teachers are too fast in explaining the material, student worksheets are incomplete, there are no practicums that support learning, students do not pay attention, and do not record the material delivered by the teacher, students do not learn before the test takes place, students are not careful in answering questions, and students only memorize the material while learning without understanding the basic concepts of the material.